M. Forcan, Z. Stojanovic, “An algorithm for sensitive directional transverse differential protection with no voltage inputs,” Electr Power Syst Res, vol. 137, pp. 86–95, Aug. 2016 (Electric power systems research, 2020)
Forcan and Stojanovic are grateful for the opportunity to further discuss the main contributions of their published article. It is their opinion that the claim "it is very difficult to find in [A] further improved protection characteristics with respect to the algorithm previously published in [B] (Ref. [3] of paper [A]), or to infer from [A] disadvantages of such a previously presented algorithm" is not argumentative and correct. To conclude, some of the case studies used in article [A] are the same as in article [B], but many others are not. Even if all case studies were similar, it is not a violation of any kind if different algorithms are used. Testing of different algorithms on the similar case studies is very common in science. It is sometimes desirable for readers to have results from different algorithms compared on the same or similar case studies.